(untitled) (Texas Journal of Engineering and Technology, 2022)
The paper deals with the issues of choosing a learning path in the Smart-education environment. A methodology for choosing a path based on the use of decision support methods is proposed, which allows using both the experience and knowledge of experts in various areas of organization and provision of the educational process, and the wishes of the student himself. The proposed methodology allows you to automate the process of choosing the most rational learning path and reduce the time to make a decision.